E-007 A1 segment patency outcomes following pipeline embolization device deployment from the distal internal carotid artery into the M1 segment. (22nd July 2018) - Pujari, A; Howard, B; Madaelil, T; Cawley, C; Grossberg, J
Abstract : Introduction: Utilization of the Pipeline Embolization Device (PED) for treating large and giant aneurysms of the distal internal carotid artery (ICA) is not well characterized. Conclusive evidence does not exist regarding flow diversion consequences related to PED placement into the M1 segment of the middle cerebral artery (MCA). Methods: A retrospective chart review of patients treated for aneurysms with PEDs that extend into the MCA. All treated at a single medical center between 2011 and the present. Patient demographics, follow-up imaging and bilateral A1 and M1 vessel diameters with pertinent ratios were recorded. Results: A total of 32 patients were included in the study (9 male, 23 female, ages 51±14 years). Follow-up angiogram was conducted at an average of 6±2 months. Seventeen (53%) patients demonstrated complete patency of the covered A1 segment and 3 (9%) patients showed narrowing of this segment. Twelve (38%) patients demonstrated occlusion of the covered A1 segment. Together, patients who maintained A1 patency and those that only showed vessel narrowing had an average A1 diameter to ipsilateral M1 segment diameter ratio of 0.70 and an average A1 diameter to contralateral A1 diameter ratio of 1.09. These values corresponded to 1.30 and 1.51 times their equivalent ratios in the patients whose A1 did not demonstrate blood flow on follow-up angiogram. Interestingly, none of the patients treated developed anterior cerebral artery (ACA) stroke or worsening of modified Rankin Score on follow-up. Two patients experienced vision loss and one patient's stent was found to be asymptomatically occluded. Conclusions: The PED can safely be used to treat aneurysms with deployment from the distal ICA into the M1 segment of MCA. Unilateral A1 segment dominance may be predictive of cerebral blood flow into the ACA following deployment at this location. Learning objectives: Identify opportunities for safe application of the Pipeline Embolization Device (PED) with coverage of the ACA. Discuss flow–related dynamics of the ICA–terminus and how they relate to PED placement and vessel dominance. Disclosures: A. Pujari: None. B. Howard: None. T. Madaelil: None. C. Cawley: None. J. Grossberg: None.